2010
DOI: 10.1007/s11856-010-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Quaternionic Monge-Ampère equation and Calabi problem for HKT-manifolds

Abstract: A quaternionic version of the Calabi problem on the Monge-Ampère equation is introduced, namely a quaternionic Monge-Ampère equation on a compact hypercomplex manifold with an HKT-metric. The equation is non-linear elliptic of second order. For a hypercomplex manifold with holonomy in SL(n, H), uniqueness (up to a constant) of a solution is proven, as well as the zero order a priori estimate. The existence of a solution is conjectured, similar to the Calabi-Yau theorem. We reformulate this quaternionic equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 17 publications
1
87
0
1
Order By: Relevance
“…It has already been solved on compact manifolds with a flat hyperKähler metric [5]. Relating to this problem, it is meaningful and interesting to study the quaternionic Monge-Ampère operator and develop pluripotential theory on quaternionic manifolds [1,4,6,16,22]. The quaternionic Monge-Ampère operator is defined as the Moore determinant of the quaternionic Hessian of u:…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…It has already been solved on compact manifolds with a flat hyperKähler metric [5]. Relating to this problem, it is meaningful and interesting to study the quaternionic Monge-Ampère operator and develop pluripotential theory on quaternionic manifolds [1,4,6,16,22]. The quaternionic Monge-Ampère operator is defined as the Moore determinant of the quaternionic Hessian of u:…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The complex Hessian equation on compact Kähler manifolds is not that geometric because the solutions do not yield Kähler metrics (see hovewer [1] for some geometric applications). Nevertheless the PDE theory is interesting on its own right, and a strong motivation for considering it is its real counterpart that has been developed some time ago thanks to the works of Trudinger, Wang, Chou and others (see [8,11,22,23,26] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to see that in this case, Ω + ∂∂ J ϕ is an HKT-form (see the proof of Proposition 4.2), hence Conjecture 4.1 implies existence of an HKT-metric Ω ′ = Ω + ∂∂ J ϕ such that the corresponding volume form is proportional to Φ. When Hol(M ) ⊂ SL(n, H), this conjecture was partly verified in [AV2]. We have shown that the solution of (4.1) is unique, and also gave a priori C 0 -bounds on its solution.…”
Section: Algebra Generated Bymentioning
confidence: 87%
“…The notion of positive (2p, 0)-forms on hypercomplex manifolds (sometimes called q-positive, or H-positive) was developed in [V4] and [AV1] (see also [AV2] and [V8]). For our present purposes, only (2, 0)-forms are interesting, but everything can be immediately generalized to a general situation Let η ∈ Λ p,q I (M ) be a differential form.…”
Section: Positive (2 0)-forms On Hypercomplex Manifoldsmentioning
confidence: 99%
See 1 more Smart Citation